2022
DOI: 10.1037/adb0000811
|View full text |Cite
|
Sign up to set email alerts
|

Beyond BASICS: A scoping review of novel intervention content to enhance the efficacy of brief alcohol interventions for emerging adults.

Abstract: Objective: Brief motivational interventions (BMIs) that include personalized drinking feedback delivered in a motivational interviewing (MI) style have demonstrated reductions in drinking across numerous clinical trials with emerging adults (EAs) ages 18-25. However, effect sizes for these BMIs are generally small to moderate and drinking reductions are often not maintained beyond short-term follow-ups. Additionally, EAs may be more interested in approaches that highlight wellness, mood enhancement, or goal pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 52 publications
0
22
0
Order By: Relevance
“…This intervention design and methodology are consistent with a personalized medicine approach that emphasizes the impact of risk pathways on patterns of alcohol use-such as genetic influences on internalizing and externalizing behavioral characteristics, negative affect, and emotion regulation-thereby generating positive outcomes that include drinking reductions. Murphy et al (2022) conducted a scoping review of brief interventions for young adults published between 2015 and 2021 that included stand-alone or expanded intervention content beyond that of traditional BMIs. They found that, although in-person BMIs This document is copyrighted by the American Psychological Association or one of its allied publishers.…”
Section: Personalized and Etiologically-informed Intervention Designmentioning
confidence: 99%
See 1 more Smart Citation
“…This intervention design and methodology are consistent with a personalized medicine approach that emphasizes the impact of risk pathways on patterns of alcohol use-such as genetic influences on internalizing and externalizing behavioral characteristics, negative affect, and emotion regulation-thereby generating positive outcomes that include drinking reductions. Murphy et al (2022) conducted a scoping review of brief interventions for young adults published between 2015 and 2021 that included stand-alone or expanded intervention content beyond that of traditional BMIs. They found that, although in-person BMIs This document is copyrighted by the American Psychological Association or one of its allied publishers.…”
Section: Personalized and Etiologically-informed Intervention Designmentioning
confidence: 99%
“…Yet, how these interventions that only indirectly address alcohol use (e.g., Fucito et al, 2017) directly impact consumption levels remains indeterminate. Consistent with Borsari et al (2012), Murphy et al (2022) suggest that a stepped-care strategy may assist in the selection or deployment of intervention options, whereby intervention modules are incrementally selected and implemented (Sobell & Sobell, 2000) such that more intensive, higher level, or multicomponent approaches may be needed for certain individuals. Though substantial research remains to determine optimal intervention(s), timing and targets, in the context of individuals' personal preferences and risk profiles, approaches that allow for greater tailoring may yield better engagement, more successful outcomes, and longer duration of intervention effects, thereby allowing for better translation of effective interventions to nonresearch settings.…”
Section: Personalized and Etiologically-informed Intervention Designmentioning
confidence: 99%
“…Overcoming the Caveats of the Field Lack of diverse representation was a major area of concern captured in what I refer to as the caveats (i.e., acknowledging limitations due to underrepresentation in samples) expressed by many articles in this special issue. Although Murphy et al (2022) in their scoping review in this issue found that sample demographics have become more diversified with time, they suggested the science would benefit from further diversification. The scoping review by Cronce et al (2022) found very limited investigation of brief interventions focused specifically on diverse subpopulations of early adults.…”
Section: Looking Forward To Multiculturalismmentioning
confidence: 95%
“…Universities may wish to incentivize participation in early adult health interventions since Rodriguez et al (2021) found that students may be more inclined to engage and persist if incentivized. Students present with many mental health challenges today (Duffy et al, 2019), prompting Murphy et al (2022) to suggest addressing comorbidity among early adults.…”
mentioning
confidence: 99%
“…Since the initial development, implementation, and evaluation of the landmark Brief Alcohol Screening and Intervention for College Students (BASICS; Dimeff et al, 1999; Larimer et al, 2021), practitioners working in colleges and universities have been provided unprecedented access to brief interventions that may be implemented across a variety of modalities, settings, subpopulations of young adults, and other intervention-related parameters (Cronce et al, 2022; Larimer et al, 2021; Rodriguez et al, 2021). Although standard in-person brief motivational interventions (BMIs) have the greatest empirical support, there are a variety of alternative intervention approaches that might enhance health and well-being and that can be feasibly integrated with BMIs or offered as an appealing “gateway” to increase help-seeking among young adults who drink alcohol (Murphy et al, 2022). With regard to the efficient uptake of brief alcohol interventions for young adults, researchers have developed recommendations for the translation of brief alcohol interventions to practice; for example, in this issue, Becker et al (2021) offer several guiding principles for researchers and clinicians seeking to implement brief interventions for young adults, including selecting an implementation model; considering contextual factors; specifying an implementation strategy; assessing implementation outcomes; and embracing hybrid effectiveness—implementation designs.…”
mentioning
confidence: 99%